Answer:
9
Step-by-step explanation:
The equation says y = x + 9
Therefore, y = 9 since x = 0 on the y axis.
Picture of graph also attached :)
Answer:
(- 4, - 10 )
Step-by-step explanation:
Given the 2 equations
y = x - 6 → (1)
x = - 4 → (2)
Substitute x = - 4 into (1) for corresponding value of y
y = - 4 - 6 = - 10
Solution is (- 4, - 10 )
Ahhh I think that is cheating?
Soz I know the anaswer but I cant tell you have to do by your self to learn you can't always ask for answers :<
To do these problems, you plug in the ‘n’ value given into the equation.
a. 6j - 3 : j = 4
6(4) - 3
24 - 3
21
b. 1/2b + 5 : b = 14
1/2(14) + 5
7 + 5
12
c. 8 + 4k : k = 3.5
8 + 4(3.5)
8 + 14
22